Yoga as a Preventive Intervention for Cardiovascular Diseases and Associated Comorbidities: Open-Label Single Arm Study - Sharma, Kaushal; Basu-Ray, Indranill; Sayal, Natasha; Vora, Ariana; Bammidi, Sridhar; Tyagi, Rahul; Modgil, Shweta; Bali, Parul; Kaur, Paramvir; Goyal, Atul Kumar; Pal, Deepak Kumar; Arvind, Harshita; et al. (Frontiers in Public Health, 2022)
Aim: Common Yoga Protocol (CYP) is a standardized yoga protocol authored by experts from all over the world under the aegis of Ministry of AYUSH, Ayurveda, Yoga & Naturopathy, Unani, Siddha, Sowa Rigpa and Homoeopathy (AYUSH). Potential of CYP can be determined as a cost-effective life style modification to prevent the risk of developing cardiovascular diseases (CVD). Methods: In this prospective trial, we compared the effect of CYP at baseline and after one-month. Three hundred seventy-five Yoga-naïve participants performed CYP under the supervision of experienced trainers. Physiological (body mass index (BMI), blood pressure, percent oxygen saturation), biochemical (fasting blood glucose and lipid profile) and neurocognitive parameters were measured before and after the intervention. Results: At day thirty of yoga practice, serum levels of low density lipoprotein (LDL), total cholesterol (TC), and high-density lipoprotein (HDL) were found significantly improved as compared to the baseline levels observed at the time of enrollment. Similarly, the lipid profile was also obtained from experienced trainers and found to be significantly different from those of yoga-naïve volunteers. When intervention was compared between the healthy yoga-naïve participants were compared with yoga-naïve participants suffering with medical issues, it was found that cholesterol profile improved significantly in the healthy group as compared to the diseased group (Hypertension, Diabetes, underwent surgery and CVD). Conclusion: These results highlight the need for further research in order to better understand the effects of yoga on primary prevention of CVD.